Economic values and selection indexes for dairy traits in Guzerat breed in Brazil - Ligori, Viviane A. [UNESP]; Cardoso, Vera L.; Peixoto, Maria Gabriela C. D.; Bruneli, Frank A. T.; Carrara, Eula R.; Zadra, Lenira E. F. [UNESP] (Springer Nature, 2025)
Economic efficiency is affected by several traits, and as the unit of selection is the individual, in artificial selection, to promote the maximization of economic genetic gain, the traits to be improved must be weighted by their respective economic values. In Brazil, breeding goals are defined empirically, and not based on an economic evaluation, therefore, the aim of this study was to estimate economic values for traits of economic importance in dairy farming systems based on the use of purebred and crossbred Guzerat animals. The economic values for 305-days milk yield (MY), fat yield (FY), protein yield (PY), and somatic cell count (SCC) were calculated for different production systems based on the feed management: System 1, based on pasture grazing with Brachiaria brizantha or Panicum maximum cv. Mombaça during rainy season, and corn-silage supplementation during the dry season; System 2, based on pasture grazing with Brachiaria brizantha or Panicum maximum cv. Mombaça during rainy season, and the mixture of sugarcane including urea supplementation during the dry season. Bioeconomic models were applied to estimate economic values, and a sensitivity analysis was performed. Four selection indexes were defined, each one with different goals: milk (I1), milk + protein yield (I2), I2 + fat yield (I3) and I3 + somatic cell count (I4). The economic values for MY and PY were positive for both production systems. However, for FY, the values were positive for System 2 but negative for System 1. The economic value for SCC was negative (-7.33 per SCS per lactation). The selection responses for I1 were higher than those for I2, I3 and I4, for both production systems. I4 presented the highest expected genetic gain for each trait, except for fat yield, whose expected genetic gain was greater with the use of I2, in both production systems. The results indicates that the inclusion of milk quality traits in the selection index provides better economic return, and due to the small differences in expected genetic superiority, I1 is still the most suitable for crossbred Guzerat herds whose main activity is milk production in Brazil.
Keywords: Animal production; Bioeconomic model; Breeding goals; Dairy cattle; Milk quality; Zebu